Effect of hen age on egg quality, hatching performance and chick quality in chukar partridges (alectoris chukar) - Mustafa Cam; Mahmut Samil Samli; Zahit Kutalmis Kaya; Halil Harman; Abdullah Bilir; Kemal Kirikci (Eurasian Journal of Veterinary Sciences)
Aim: This study was aimed to investigate the effect of different hen ages on egg quality characteristics, hatching performance and chick quality in chukar partridges. Materials and Methods: A total of 510 eggs obtained from chukar partridge flocks were used to determine the effects of different hen age on hatching performance, egg quality traits and chick quality. Daily collected 20 eggs from each age group (1, 2 and 3 years of age) were assessed for internal quality characteristics. A total of 150 eggs per each age group were set into incubator and hatcher set. After hatching, unhatched eggs were broken to determine hatching performance and embryonic mortality. Hatched day-old chicks were scored to determine chick quality characteristics. Results: Internal egg quality traits were not statistically affected by different breeding ages. Different breeding ages did not affect hatchability, early and middle embryonic mortality while late embryonic mortality and fertility of eggs were statistically affected. The evaluated chick quality traits were affected by the different hen age. Conclusion: Despite decreasing fertility rate with age, the results of this study suggest incubating eggs of chukar hens with 3 years age for optimum chick quality and being raised chukar hens up to 3 years of age.